Binding, Thermodynamics, and Selectivity of a Non-peptide Antagonist to the Melanocortin-4 Receptor - Saleh, Noureldin; Kleinau, Gunnar; Heyder, Nicolas; Clark, Timothy; Hildebrand, Peter W.; Scheerer, Patrick (Frontiers in Pharmacology, 2018)
The melanocortin-4 receptor (MC4R) is a potential drug target for treatment of obesity, anxiety, depression and sexual dysfunction. Crystal structures for MC4R are not yet available, which has hindered successful structure-based drug design (SBDD). Using microsecond-scale molecular-dynamics simulations, we have investigated selective binding of the non-peptide antagonist MCL0129 to a homology model of human MC4R (hMC4R). This approach revealed that, at the end of a multi-step binding process, MCL0129 spontaneously adopts a binding mode in which it blocks the agonistic-binding site. This binding mode was confirmed in subsequent metadynamics simulations, which gave an affinity for human hMC4R that matches the experimentally determined value. Extending our simulations of MCL0129 binding to hMC1R and hMC3R, we find that receptor subtype selectivity for hMC4R depends on few amino acids located in various structural elements of the receptor. These insights may support rational drug design targeting the melanocortin systems.